Popularization of environmental culture through digital education and online courses in phytodesign - Brovarna, Yevheniia (Педагогічна Академія: наукові записки, 2025)
The study’s relevance stems from the growing need to foster an ecological culture among the population, in the context of urbanisation and increased public demand for biophilic and greening practices. The article aims to substantiate holistic scientific approaches and digital educational solutions that can ensure the effective popularisation of ecological culture through online courses and integrated programs in phytodesign, interior landscaping, and plant therapy. The research methodsinclude content analysis of digital educational platforms, comparative analysis of eco-education models, generalisation of pedagogical, ecological, and psychological sources, and systematisation of data on the use of virtual laboratories, augmented reality (AR), and virtual reality (VR) technologies in modelling green spaces. Results. It has been established that digital formats – microlearning, video modules, AR/VR modelling, interactive cases, virtual laboratories – are suitable for providing practice-oriented learning, reproducing real care scenarios, and developing students’ cognitive, activity, and value-behavioural competencies. It has been found that combining phytodesign with elements of plant therapy enhances students’ psycho-emotional involvement and contributes to the formation of sustainable environmental habits. It has been proven that digital programs become effective only when they feature modular, scientifically verified content, personalised tasks, and the ability to track educational progress analytically. Conclusions. Digital eco-education is a promising tool for scaling ecological culture, as it reaches a broad audience and creates conditions for the systematic development of environmentally friendly behaviour. Comprehensive phytodesign programs that combine ecological, design, and therapeutic components clarify the mechanisms of perception and the practical application of ecological knowledge, facilitating the transition from theoretical awareness to real, sustainable actions in everyday life. Prospects for further research are related to the creation of standardised requirements for the quality of digital eco-courses, the development of intelligent adaptive educational platforms, the expansion of AR/VR environments for modeling complex biophysical processes in educational programs, as well as conducting longitudinal pedagogical studies aimed at assessing the impact of digital ecological education on sustainable behavioral practices of different population groups.